Composto orgânico no potencial fisiológico de sementes de brócolis após o armazenamento - Magro, Felipe Oliveira [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP]; Fernandes, Dirceu Maximino [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The study was carried out with the objective to evaluate the broccoli seeds (cultivar Ramoso Santana) germination and vigor from plants cultivated with different organic compost levels and after storage in dry chamber. At seed production stage, the experiment was conducted in randomized complete blocks design, with five treatments (0; 30; 60; 90 and 120 t ha(-1) of Biomix (R) organic compost) and four replications. Soon after harvesting and after 12 and 24 months of conservation in dry chamber room (20 degrees C and 40% relative humidity) it was evaluated germination, following seed analisys rules, and vigor (first count of germination and germination speed index - IVG). There were no differences in germination and vigor in seeds as soon as they were harvested and after 12 month of storage. After 24 months of storage, the lesser the organic compost rates, the lesser seed germination and IVG, with respective values, without compost, of 69% and 12,3. For another hand, the highest values for germination and IVG, 82% and 16,1, respectively, were obtained with the highest rate of organic compost (120 t ha(-1)).
Organic compost in physiological potential of broccoli seeds after storage
Keywords: Brassica oleracea var. italica; organic fertilization; germination